Housing the Homeless and Poor : New Partnerships among the Private, Public, and Third Sectors. - Fallis, George (University of Toronto Press, 1991)
Ultimately, Multiversities, Ideas, and Democracy seeks to uncover the ethos of the multiversity and to hold such institutions accountable for their contribution to democratic life. It will appeal to anyone interested in the role of education in society.